MONITORING AND ANALYSIS OF STUDENTS' PERFORMANCE DURING SOFTWARE DEVELOPMENT - Oleksandr Sharyhin; Vasyl Fedorets; Oksana Klochko (Інформаційні технології і засоби навчання)
This study presents a comprehensive approach to monitoring and analyzing students’ performance in the context of software development projects. The primary focus is on the development of novel performance metrics that effectively capture the level of control required from the Team Leader and the quality of work assessed by the QA Engineer. The introduced metrics, namely Relative Control Degree and Relative Quality Assurance Degree, offer a robust framework for evaluating and understanding students’ performance across project, company, and industry levels.